2020
DOI: 10.1177/1468087420916683
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of knock severity in a Cooperative Fuel Research engine using binary gasoline–alcohol blends

Abstract: Knock remains one of the main limitations for increasing the efficiency in spark-ignition engines. The use of certain alcohol–gasoline blends is an effective way to either mitigate or eliminate knock, allowing the use of higher compression ratios, therefore increasing the efficiency of spark-ignition engines. Methanol and ethanol are alcohols commonly employed for reducing knock, due to their higher octane number and vaporization heat value. Major attention is being paid recently to butanol and its blends with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…6 Also, it is stored in large quantities in hydrocarbons, water, and other organic matters. Recently, many investigators revealed that a reliable way for improving fuels' capabilities and achieving the best efficiency for internal combustion engines (ICEs) is to blend those that have superior combustion features together, see Schifter et al, 7 Corral-Go´mez et al, 8 Hua et al, 9 and Bermu´dez et al 10 Furthermore, hydrogen-enriched compress natural gas (HCNG) includes the privileges of both methane and H 2 . Hydrogen is a beneficial gas for improving the flame rate corresponding to combustion and engine stability in a spark-ignition (SI)-compress natural gas (CNG) engine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Also, it is stored in large quantities in hydrocarbons, water, and other organic matters. Recently, many investigators revealed that a reliable way for improving fuels' capabilities and achieving the best efficiency for internal combustion engines (ICEs) is to blend those that have superior combustion features together, see Schifter et al, 7 Corral-Go´mez et al, 8 Hua et al, 9 and Bermu´dez et al 10 Furthermore, hydrogen-enriched compress natural gas (HCNG) includes the privileges of both methane and H 2 . Hydrogen is a beneficial gas for improving the flame rate corresponding to combustion and engine stability in a spark-ignition (SI)-compress natural gas (CNG) engine.…”
Section: Introductionmentioning
confidence: 99%
“…6 Also, it is stored in large quantities in hydrocarbons, water, and other organic matters. Recently, many investigators revealed that a reliable way for improving fuels’ capabilities and achieving the best efficiency for internal combustion engines (ICEs) is to blend those that have superior combustion features together, see Schifter et al, 7 Corral-Gómez et al, 8 Hua et al, 9 and Bermúdez et al 10…”
Section: Introductionmentioning
confidence: 99%
“…The use of CFR engine for experimental determination of combustion characteristics is common in literature. [8][9][10][11] However, the numerical simulation of CFR engine is sparse. Recently, Garcı´a et al 12 have developed a virtual 1-D model of CFR engine with GT Power.…”
Section: Introductionmentioning
confidence: 99%
“…12 Various indexes can be found to evaluate the knock content [13][14][15] but the maximum amplitude of pressure oscillations (MAPO) is one of the most common. 16,17 The MAPO is obtained by high-pass filtering the measured in-cylinder pressure trace every cycle and a threshold is traditionally determined empirically from experimental data by the user to avoid engine damage. When combustion conditions lead to unsafe operation where spontaneous auto-ignition of the end gas appears, the MAPO is detected above this limit and the cycle is considered as knocking.…”
Section: Introductionmentioning
confidence: 99%